Decellularized Swine Dental Pulp Tissue for Regenerative Root Canal Therapy. (December 2018) - Alqahtani, Q.; Zaky, S.H.; Patil, A.; Beniash, E.; Ray, H.; Sfeir, C.
In the current theme of dental pulp regeneration, biological and synthetic scaffolds are becoming a potential therapy for pulp revitalization. The goal is to provide a suitable environment for cellular infiltration, proliferation, and differentiation. The extracellular matrix (ECM) represents a natural scaffold material resembling the native tissue chemical and mechanical properties. In the past few years, ECM-based scaffolds have shown promising results in terms of progenitor cells recruitment, promotion of constructive remodeling, and modulation of host response. These properties make ECM-derived scaffolds an ideal candidate for pulp regenerative therapy. Development of strategies for clinically relevant tissue engineering using dental pulp extracellular matrix (DP-ECM) can provide an alternative to conventional root canal treatment. In this work, we successfully decellularized ECM derived from porcine dental pulp. The resulting scaffold was characterized using immunostaining (collagen type I, dentin matrix protein 1, dentin sialoprotein, and Von Willebrand factor) and enzyme-linked immunosorbent assay (transforming growth factor β, vascular endothelial growth factor, and basic fibroblast growth factor) for extracellular proteins where the ECM retained its proteins and significant amount of growth factors. Furthermore, a pilot in vivo study was conducted where the matrix was implanted for 8 wk in a dog root canal model. Our in vitro and preliminary in vivo data show that the decellularized ECM supports cellular infiltration together with the expression of pulp-dentin and vascular markers (DSP and CD31) compared to the controls. Herein, we show the feasibility to produce a decellularized ECM scaffold and validate the concept of using ECM-based scaffolds for pulp regeneration.